“Spill the Tea” as a Metaphor for Privacy Conflict and Truth Construction on Twitter - Nisa, Nadia Najwa Khairun; Jannah, Himatul; Izzatunnisa, Azka (Cultural Narratives, 2025)
This research aims to reveal the clash between the public and private spheres in using the slang ‘spill the tea’ on Twitter. The theory used in this research is the theory of metaphor by Roman Jakobson. This research is qualitative in its nature in which the data are used in a various context if issue. The findings in this research show that the use of the slang 'spill the tea' establishes a conflict between the perceived privacy of specifically social media interactions on twitter and the reality of public exposure. This research reveals that the structure of Twitter can make untrue information true without making private information appear in public, or anonymous, spaces. In addition, the findings also emphasize how the metaphorical nature of gossip, embedded in slang, reflects larger social dynamics regarding truth in the context of gossip. The findings of this research indicate that the slang “spill the tea” serves as a metaphorical lens through which the tension between perceived privacy and actual public exposure on Twitter is revealed. This highlights how digital platforms transform social interactions by allowing users to engage in gossip under the illusion of anonymity, while the platform’s viral nature can rapidly shift private information into the public domain. Ultimately, the study concludes that language, particularly metaphor embedded in slang, plays a critical role in shaping narratives and social dynamics around truth and privacy in online spaces.